Technical Performance and Economic Feasibility Simulation of 200kWP Rooftop Solar Photovoltaic On grid on Industrial Estate Factory Building with Helioscope Software - Dhami Johar Damiri; Achmad Aditya Nugraha (Universitas Syiah Kuala, 2021)
Renewable energy resources are currently being developed in Indonesia. The government is also targeting renewable energy mix of 23% to be achieved in 2025. Solar Photovoltaic Generation System is one of a form of renewable energy that is currently being developed in Indonesia. Several industrial estates in Indonesia are filled with factories with fairly large buildings and have great potential for the development of Rooftop Solar Photovoltaic with the advantage of reducing land investment costs and of course without reducing the functionality of factory operational. The purpose of this research is to simulate the technical and economic performance of Solar Photovoltaic on grid 200kWP installed on the roof of a factory building using Helioscope software in an industrial estate area in West Java. The simulation results show that the average value for Global Horizontal Irradiance (GHI) is 138.2 kWh/m2, Electrical Energy Production is 21,977 kWh, and the Performance Ratio (PR) in one year is 78.06. Meanwhile, the total annual Electrical Energy Production is 263,723.6 kWh. The total investment value of the Rooftop Solar Photovoltaic on Grid system in this factory building is Rp. 2,457,850,800. Based on the economic feasibility study made, it can be concluded that the Rooftop Solar Photovoltaic on Grid system with a power of 200 kWP in the factory building is economically feasible as long as the interest rate is less than 12.71% (Internal Rate of Return/ IRR).